Las visiones de Raúl Zurita y el prejuicio de lo sublime - Geneviève Fabry (Caravelle)
This article examines the reach of performative utterance in the poetry of the Chilean Raúl Zurita (1950- ) in poem collections linked with de cycle of « the new life » (Purgatorio, 1979 ; Purgatorio, 1982 ; La vida nueva, 1994 ; Cuadernos de Guerra, 2009). To examine Zurita’s strategies (specially the association of poetry and land art) as expressions of the esthetics of sublime, as Kant, Lyotard and Saint Girons define it, permits to project a new light upon this most puzzling work and, at the same time, to determine more accurately what is at stake in the controversies it engenders (above all, consult the criticisms by Nelly Richard and Roberto Bolaño).